2006
DOI: 10.1002/jbm.a.30680
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton excited fabricated nano and micro patterned extracellular matrix proteins direct cellular morphology

Abstract: We use multiphoton excited (MPE) photochemistry to fabricate patterned extracellular matrices (ECM) and to investigate the morphology of human dermal fibroblasts adhered to the resulting photocrosslinked linear structures of fibronectin (FN), fibrinogen (FG), and bovine serum albumin (BSA). These proteins were chosen to systematically investigate the roles of topography and ECM biochemistry on cell spreading, as fibroblasts bind directly to both FN and FG at RGD sites through known integrins, whereas BSA provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 71 publications
3
41
0
Order By: Relevance
“…Although the studies reported here focus on the use of BSA-based microstructures modified via avidin-biotin interactions, the Shear group and others have also successfully employed MPE techniques to crosslink other bioactive proteins, including various enzymes, while retaining substantial activity. [14][15][21][22][23][24] Additionally, the Shear group has previously demonstrated the feasibility for creating metalized, conductive protein-based microstructures, [23] materials potentially useful in applications such as nerve regeneration, where a combination of electrical stimulation, chemical gradients, and physical guidance may be required. [18] …”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Although the studies reported here focus on the use of BSA-based microstructures modified via avidin-biotin interactions, the Shear group and others have also successfully employed MPE techniques to crosslink other bioactive proteins, including various enzymes, while retaining substantial activity. [14][15][21][22][23][24] Additionally, the Shear group has previously demonstrated the feasibility for creating metalized, conductive protein-based microstructures, [23] materials potentially useful in applications such as nerve regeneration, where a combination of electrical stimulation, chemical gradients, and physical guidance may be required. [18] …”
Section: Full Papermentioning
confidence: 99%
“…[20] By scanning the laser focus relative to reagent solution, it is possible to create structures with arbitrary 3D morphology and low-to submicrometer features. [14][15][21][22][23][24][25][26][27] After fabrication, protein guidance paths are decorated with laminin-derived peptides, using avidin-biotin linkages, to promote cell adhesion and migration.…”
mentioning
confidence: 99%
“…ECM proteins (like fibrinogen, fibronectin, collagen) as biocompatible scaffold materials were microstructured via singlet oxygen crosslinking using sensitizing dyes [70] even inside living cells. [71,72] Catalytically active microstructures have been made by 2PP via Rose Bengale crosslinking using enzymes as building material. [73,74] One of the most serious drawbacks of the 2PP technology is the inherent serial, voxel-by-voxel character of the fabrication process resulting in extended processing times.…”
mentioning
confidence: 99%
“…Micropatterning has been widely used as a method of controlling cell morphology, spatial arrangement, and function [27,28] by imparting various types of cell-scale guidance cues by controlling regions of adhesion [25,[29][30][31], topology [32][33][34][35][36][37], and "direct writing" of scaffolds and cells [38][39][40]. A common method used in many of these approaches involves a set of techniques known as soft lithography [41].…”
Section: Introductionmentioning
confidence: 99%